Maternal and Fetal Outcomes Among Pregnant Women With Human Monkeypox Infection in the Democratic Republic of Congo - Mbala, Placide K.; Huggins, John W.; Riu-Rovira, Therese; Ahuka, Steve M.; Mulembakani, Prime; Rimoin, Anne W.; Martin, James W.; Muyembe, Jean-Jacques T. (The Journal of infectious diseases, 2017)
Human monkeypox is an endemic disease in rain-forested regions of central Democratic Republic of Congo. We report fetal outcomes for 1 of 4 pregnant women who participated in an observational study at the General Hospital of Kole (Sankuru Province), where 222 symptomatic subjects were followed between 2007 and 2011. Of the 4 pregnant women, 1 gave birth to a healthy infant, 2 had miscarriages in the first trimester, and 1 had fetal death, with the macerated stillborn showing diffuse cutaneous maculopapillary skin lesions involving the head, trunk and extremities, including palms of hands and soles of feet.